2016
DOI: 10.4236/fns.2016.711098
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Utilization of Corn Pericarp and Peanut Hull in the Production of Ethanol and the Impact on Food Economics

Abstract: Corn pericarp and peanut hull (lignocellulosic materials) which are food industry by-products were used as substrates in this study. Alkaline hydrogen peroxide (H 2 O 2) pretreatments at 0%, 2.5% and 5% were used for the removal of lignin. Simultaneous Saccharification and Fermentation (SSF) and Separate Hydrolysis and Fermentation (SHF) were conducted using Aspergillus niger (strain 201201) and Saccharomyces cerevisiae (strain 26603). Aspergillus niger was added on day 1 to all samples with inoculation treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The best approach therefore is co-digestions with other energy-yielding substrates as this will enhance substrate synergy and higher microbial diversity leading ultimately to higher biogas yield (Khoufi et al, 2015). Despite the abundance of peanut hulls globally, only few attempts have been documented for its utilization for biofuel generation and such studies focused majorly on ethanol and isoprene productions (Herring and Narayanan, 2016;Polachini et al, 2016;Wang et al, 2016) while its usage for biogas generation is grossly under-reported. Though the potential of the hull for biogas generation in mono-digestion was reported in our recent study (Dahunsi et al, 2017b), the potential synergistic effects in its co-digestion with other substrates in order to improve digestibility and biogas yield is yet to be understood and this was addressed in this research.…”
Section: Introductionmentioning
confidence: 99%
“…The best approach therefore is co-digestions with other energy-yielding substrates as this will enhance substrate synergy and higher microbial diversity leading ultimately to higher biogas yield (Khoufi et al, 2015). Despite the abundance of peanut hulls globally, only few attempts have been documented for its utilization for biofuel generation and such studies focused majorly on ethanol and isoprene productions (Herring and Narayanan, 2016;Polachini et al, 2016;Wang et al, 2016) while its usage for biogas generation is grossly under-reported. Though the potential of the hull for biogas generation in mono-digestion was reported in our recent study (Dahunsi et al, 2017b), the potential synergistic effects in its co-digestion with other substrates in order to improve digestibility and biogas yield is yet to be understood and this was addressed in this research.…”
Section: Introductionmentioning
confidence: 99%